2006
DOI: 10.1161/01.str.0000209332.96513.82
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge About Risk Factors for Stroke

Abstract: Background and Purpose-Increased knowledge of stroke risk factors in the general population may lead to improved prevention of stroke. The objective of the present study was to assess knowledge of stroke risk factors and to determine factors associated with knowledge. Methods-In a population-based survey, we sent a questionnaire to randomly selected residents in Berlin who were Ն50 years of age enquiring about knowledge of stroke risk factors. Knowledge was assessed in an open-ended question. In addition, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
59
2
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 29 publications
(26 reference statements)
3
59
2
1
Order By: Relevance
“…However, less than one third of the general public can come up with more than two symptoms or risk factors and even fewer are considered to have an adequate knowledge of stroke or TIA. Similar results have been reported throughout the United States and across Europe and Asia (Kothari et al 1997, Pancioli et al 1998, Yoon et al 2001, Reeves et al 2002, Greenlund et al 2003, Parahoo et al 2003, Centers for Disease Control and Prevention 2004, Ferris et al 2005, Müller-Nordhorn et al 2006, Nedeltchev et al 2007, Evci et al 2007, Mikulík et al 2008. Women have been found to have a better overall symptom awareness and knowledge of risk factors than men (Ferris et al 2005).…”
Section: Knowledge Of Stroke Among the Publicsupporting
confidence: 75%
See 1 more Smart Citation
“…However, less than one third of the general public can come up with more than two symptoms or risk factors and even fewer are considered to have an adequate knowledge of stroke or TIA. Similar results have been reported throughout the United States and across Europe and Asia (Kothari et al 1997, Pancioli et al 1998, Yoon et al 2001, Reeves et al 2002, Greenlund et al 2003, Parahoo et al 2003, Centers for Disease Control and Prevention 2004, Ferris et al 2005, Müller-Nordhorn et al 2006, Nedeltchev et al 2007, Evci et al 2007, Mikulík et al 2008. Women have been found to have a better overall symptom awareness and knowledge of risk factors than men (Ferris et al 2005).…”
Section: Knowledge Of Stroke Among the Publicsupporting
confidence: 75%
“…(Pancioli et al 1998, Parahoo et al 2003, Evci et al 2007) The sources of information have also varied considerably between different age groups and study settings. (Müller-Nordhorn et al 2006) The most commonly mentioned warning symptoms in these surveys have been…”
Section: Knowledge Of Stroke Among the Publicmentioning
confidence: 99%
“…We found that 84.3% of patients spontaneously named at least one risk factor while most studies reported percentages that range 40 to 79% [13,16,18,20,[32][33][34][35][36][37][38][39][40][41].…”
Section: Discussionmentioning
confidence: 79%
“…İnme risk faktörleri bilgi düzeyinin yaşla arttığı, eğitim düzeyi ile düştüğü farklı çalışmalarda gösterilmiştir (14)(15)(16)(17)(18). İnme semptomları bilgi düzeyinin genç yaş, bayan cinsiyet, yüksek eğitim düzeyi, hipertansiyon öyküsü, geçirilmiş inme, sigara içimi ve yüksek gelir düzeyi ile arttığını gösteren çalışmalar bulunmaktadır (19,20).…”
Section: Discussionunclassified